The Development of Poem Instructional Module Based on Dick and Carey's Instructional System Design - Amzah, Fadzilah bt; Zakaria, Haniza (Faculty of Psychology, Universitas Surabaya, 2008)
The purpose of this study was to develop the Poem Instructional Module Based on Reader Response Approach (PIMBRRA). The module was developed based on Dick & Carey’s Instructional System Design. Dick & Carey’s Model was selected because it consists of comprehensive and syste- matic instructional planning processes, comprising of developmental phases of module development, a thorough evaluation and revision process, and testing process. This study consists of two phases, i.e. the development of PIMBRRA phase and the Formative Evaluation phase. The development of PIMBRRA phase adopted steps one through seven of Dick & Carey’s Model. The Formative Evalua- tion phase involved experts in the field of education and Malay language and literature studies, and students. Data was garnered from evaluation forms, and interviews involving three experts, teachers and students. The three categories of respondents had given positive feedback on the module. Tujuan studi ini adalah mengembangkan Poem Instructional Module Based on Reader Res- ponse Approach (PIMBRRA). Modul ini dikembangkan berdasarkan Dick & Carey’s Instructional System Design. Model Dick & Carey yang dipilih karena mengandung proses perencanaan instruk- sional yang terpadu dan sistematik, terdiri atas tahapan pengembangan dari perkembangan modul, proses evaluasi dan revisi yang ketat, dan proses pengujian. Studi ini terdiri atas dua tahapan, yaitu pengembangan tahapan PIMBRRA dan tahapan Evaluasi Formatif. Tahapan pengembangan PIMBRRA mengadopsi langkah satu hingga tujuh dari model Dick & Carey. Tahapan evaluasi forma- tif meliputi pakar dalam bidang pendidikan serta bahasa dan literatur Malaya, dan para mahasiswa. Data dikumpulkan dari format evaluasi, dan wawancara terhadap tiga pakar, guru dan siswa. Ketiga kategori responden telah memberikan balikan positif terhadap modul ini.